HOT-ROLLED STEEL SHEET AND ITS MANUFACTURING METHOD
Patent Information
- Application Number
- JP2021000186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-16
- Filing Date
- 2021-01-04
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-01-04
AI Technical Summary
【0015】 本発明によれば、強度-延性バランスに優れ、かつ高降伏比を有する鋼材を得ることが可能になる。
Smart Images

Figure 0007633492000005 
Figure 0007633492000001 
Figure 0007633492000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel material and a method for producing the same. [Background technology]
[0002] It is known that the finer the steel structure, the higher its strength, ductility, and toughness. For example, in a multi-phase steel in which hard martensite is dispersed in a soft matrix, the steel with many finely dispersed martensite particles has superior ductility and toughness compared to a steel with the same martensite volume fraction in which the martensite particles are coarsened and connected.
[0003] Furthermore, when retained austenite is contained in the structure, the austenite undergoes strain-induced martensitic transformation when strain is introduced. Therefore, steel containing retained austenite in the structure has excellent ductility and high strength, resulting in an excellent balance between strength and ductility.
[0004] DP steel or retained austenite steel is known as a material with an excellent balance of strength and ductility. For example, Patent Document 1 discloses a high-strength thin steel plate with excellent rigidity, which has a tensile strength of 590 MPa or more, a yield ratio of 0.65 or more, and a Young's modulus of 225 GPa or more.
[0005] Patent Document 2 discloses a high-strength cold-rolled steel sheet that has high absorbed energy in a low strain range and excellent crash resistance even without the introduction of strain by press working, for use in automobiles, home appliances, machine structures, etc. Furthermore, Patent Document 3 discloses a high-strength cold-rolled steel sheet that has excellent elongation and stretch flangeability and a high yield ratio. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-92131 A [Patent Document 2] JP 2008-231480 A [Patent Document 3] JP 2015-34326 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the steels described in Patent Documents 1 to 3 have a problem in that the composition must be strictly restricted in order to control the structure, and therefore there is a concern that the freedom in the chemical composition is low, leading to an increase in production costs.
[0008] The present invention has been made to solve the above problems, and has an object to provide a steel material having an excellent balance of strength and ductility and a high yield ratio. [Means for solving the problem]
[0009] The present invention relates to the following steel material and a method for producing the same.
[0010] (1) Chemical composition, in mass%, C: 1.00% or less, Si:3.00% or less, Mn: 0.2-7.0%, P: 0.10% or less, S: 0.030% or less, Al: 3.00% or less, N: 0.010% or less, Ni: 0-10.0%, Cu: 0-3.0%, Cr: 0-10.0%, Ti: 0-1.0%, Nb: 0-1.0%, V: 0-1.0%, Mo: 0-2.0%, W: 0-1.0%, B: 0~0.01%, Co: 0-1.0%, Ca: 0-0.01%, Mg: 0 to 0.01%, REM: 0~0.01%, The balance is Fe and impurities. Ceq defined by the following formula (i) is 0.10 to 1.00, The metal structure is, by volume percent, Retained austenite: 5.0 to 15.0%, and The total volume fraction of martensite and bainite is 2.5 to 50.0%; The total volume fraction of retained austenite, martensite, tempered martensite and bainite is 75.0% or more, The average grain size of the retained austenite is 2.0 μm or less. The average grain size of martensite and bainite is 5.0 μm or less, The number fraction of retained austenite having an aspect ratio of 4.0 or more is 10 to 70% of the total number fraction of retained austenite in the steel material. Steel material. Ceq=C+1 / 24Si+1 / 6Mn+1 / 40Ni+1 / 5Cr+1 / 4Mo+1 / 14V (i) In the formula, each element symbol represents the content (mass%) of each element contained in the steel, and 0 is substituted when the element is not contained.
[0011] (2) The chemical composition is, in mass%, Ni: 0.1 to 10.0%, Cu: 0.3-3.0%, and Cr: 0.1-10.0%, Contains one or more selected from The steel material described in (1) above.
[0012] (3) The chemical composition is, in mass%, Ti: 0.01 to 1.0%, Nb: 0.01 to 1.0%, V: 0.01 to 1.0%, Mo: 0.05-2.0%, W: 0.05 to 1.0%, B: 0.0003 to 0.01%, and Co: 0.05-1.0%, Contains one or more selected from The steel material according to (1) or (2) above.
[0013] (4) The chemical composition is, in mass%, Ca: 0.0001 to 0.01%, Mg: 0.0001 to 0.01%, and REM: 0.0001~0.01%, Contains one or more selected from The steel material according to any one of (1) to (3) above.
[0014] (5) Having a chemical composition according to any one of (1) to (4) above, A steel material having a metal structure mainly composed of martensite or tempered martensite, Heat the material to a temperature range of not less than the Ac1 point and not less than (Ac1 point + 3 × Ac3 point) / 4 without recrystallization, and then start cooling within 2 seconds to a temperature of not more than 100°C so that the average cooling rate from the temperature range to 300°C is 3 to 150°C / s. Steel manufacturing method. Effect of the Invention
[0015] According to the present invention, it is possible to obtain a steel material having an excellent balance of strength and ductility and a high yield ratio. [Brief description of the drawings]
[0016] [Figure 1] Graph showing (a) the relationship between tensile strength and yield ratio, and (b) the relationship between tensile strength and elongation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors have conducted extensive research into a method for obtaining a steel material having an excellent balance of strength and ductility and a high yield ratio, and as a result have arrived at the following findings.
[0018] (a) In order to achieve both high strength and excellent ductility and to obtain a high yield ratio, it is preferable that the metal structure contains finely dispersed retained austenite, martensite, and bainite, and the other base parts are mainly composed of tempered martensite.
[0019] (b) By heating the steel material to the ferrite / austenite two-phase region without recrystallization, ultrafine austenite grains are generated in part of the metal structure at high temperatures. Then, by immediately cooling from that state, finely dispersed retained austenite, martensite, and bainite are obtained.
[0020] (c) The degree of fineness after heating varies greatly depending on the structure of the steel material before heating. It is preferable to use a steel material with many austenite nucleation sites in the metal structure. Therefore, it is preferable to use a steel material with a metal structure mainly composed of martensite or tempered martensite.
[0021] (d) The untransformed regions after heating, i.e., the regions in which martensite or tempered martensite remains, are tempered to become tempered martensite.
[0022] (e) When heating is performed at a fast rate, the temperature at which the transformation to austenite is completed (Ac3 point) increases, making it possible to temper the initial martensite in a short period of time at high temperatures.
[0023] (f) The ultrafine austenite grains that are generated tend to grow into coarse grains due to grain boundary migration at high temperatures. Therefore, cooling is started immediately after heating to allow the material to cool to room temperature while maintaining the ultrafine structure.
[0024] (g) On the other hand, by slowing down the cooling rate to a certain extent, the tempered martensite is softened and softer ferrite is formed in the matrix. In addition, the formation of ferrite concentrates carbon in the austenite, which has the effect of stabilizing the retained austenite.
[0025] (h) In order to prevent the growth and coarsening of ultrafine austenite grains, it is also effective to lower the transformation temperature. Since the movement of grain boundaries is caused by the diffusion of atoms, lowering the temperature and slowing down the diffusion rate makes it possible to maintain fine grains.
[0026] (i) By adjusting the content of Mn, etc., it is possible to lower the transformation temperature of the steel material.
[0027] (j) Retained austenite undergoes work-induced transformation to martensite during deformation, suppressing local deformation and improving elongation. The ease of martensite transformation is affected by the shape of the retained austenite, and grains with higher aspect ratios tend to be more difficult to transform. Therefore, by mixing grains with high and low aspect ratios in a specified ratio, the retained austenite transforms to martensite at various times during deformation, and as a result, the effect of improving elongation can be obtained more efficiently.
[0028] The present invention has been made based on the above findings. Each feature of the present invention will be described in detail below.
[0029] (A) Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0030] C: 1.00% or less C is an element that improves the strength of steel. The C content is selected according to the properties required of the steel, but if it exceeds 1.00%, the Mf point will be too low, and some or all of the austenite generated during heating will not transform during cooling, and the required amount of martensite may not be obtained, resulting in insufficient strength. Therefore, the C content is set to 1.00% or less. The C content is preferably 0.50% or less, and more preferably 0.35% or less. To obtain the above effects, the C content is preferably 0.03% or more.
[0031] Si:3.00% or less Silicon is an element that is distributed to the ferrite phase, and in order to suppress the growth and coarsening of the ultrafine austenite structure, it is necessary to add more silicon than is normally added for deoxidation. However, if the silicon content exceeds 3.00%, the hot workability deteriorates and the steel is prone to cracking during rolling. Therefore, the silicon content is set to 3.00% or less. The silicon content is preferably 2.50% or less. In order to obtain the above effects, the silicon content is preferably 0.01% or more, and more preferably 0.03% or more.
[0032] Mn: 0.2-7.0% Mn is an effective element for lowering the growth and coarsening rate of the austenite phase by lowering the A1 transformation point and lowering the austenite formation temperature range. Mn is also an element that is distributed to the austenite phase. Furthermore, it is an effective element when retained austenite is to be utilized. In order to suppress the growth and coarsening of the ultrafine austenite structure, it is necessary to contain 0.2% or more. On the other hand, if the Mn content exceeds 7.0%, the Mf point is lowered too much, and some or all of the austenite generated during heating may not transform during cooling, and the required amount of martensite may not be obtained, resulting in insufficient strength. Therefore, the Mn content is set to 0.2 to 7.0%. The Mn content is preferably 5.0% or less, more preferably 3.0% or less.
[0033] P:0.10% or less P is generally contained as an impurity, but it is also an element that has the effect of increasing strength by solid solution strengthening. Therefore, P may be actively contained. However, P is an element that easily segregates, and if its content exceeds 0.10%, the deterioration of formability and toughness due to grain boundary segregation becomes significant. Therefore, the P content is set to 0.10% or less. The P content is preferably 0.050% or less, more preferably 0.030% or less, and even more preferably 0.020% or less. There is no need to specify a lower limit for the P content, but if the above effect is to be obtained, it is preferable to set it to 0.001% or more.
[0034] S: 0.030% or less S is an element contained as an impurity, and forms sulfide-based inclusions in steel, thereby reducing the formability of the steel sheet. If the S content exceeds 0.030%, the formability is significantly reduced. Therefore, the S content is set to 0.030% or less. The S content is preferably 0.010% or less, more preferably 0.005% or less, and even more preferably 0.001% or less. There is no particular need to specify a lower limit for the S content, but from the viewpoint of suppressing an increase in refining costs, it is preferably set to 0.0001% or more.
[0035] Al: 3.00% or less Al is an element distributed to the ferrite phase, and in order to suppress the growth and coarsening of the ultrafine austenite structure, it is necessary to add more Al than the amount normally contained for deoxidation. However, if the content exceeds 3.00%, the hot workability deteriorates and the steel is prone to cracking during rolling. Therefore, the Al content is set to 3.00% or less. The Al content is preferably 2.50% or less, and more preferably 2.00% or less. In order to obtain the above effect, the Al content is preferably 0.01% or more, and more preferably 0.03% or more.
[0036] N: 0.010% or less N is an element contained as an impurity and has the effect of reducing the formability of steel sheet. If the N content exceeds 0.010%, the formability is significantly reduced. Therefore, the N content is set to 0.010% or less. The N content is preferably 0.0080% or less, and more preferably 0.0070% or less. There is no need to specify a lower limit for the N content, but in consideration of the case where one or more of Ti, Nb, and V are contained to refine the steel structure as described below, the N content is preferably 0.0010% or more, and more preferably 0.0020% or more in order to promote the precipitation of carbonitrides.
[0037] In addition to the above elements, the steel material according to the present invention may further contain one or more elements selected from Ni, Cu, Cr, Ti, Nb, V, Mo, W, B, Co, Ca, Mg and REM in the amounts shown below.
[0038] Ni: 0 to 10.0% Ni is an element that is effective in lowering the growth and coarsening rate of the austenite phase by lowering the A1 transformation point and lowering the austenite formation temperature range. Ni is also an element that is distributed to the austenite phase. Therefore, Ni may be contained as necessary. However, when the Ni content exceeds 10.0%, the effect of suppressing grain growth becomes saturated. Therefore, the Ni content is set to 10.0% or less. The Ni content is preferably set to 5.0% or less. In order to obtain the above effect, the Ni content is preferably set to 0.1% or more.
[0039] Cu: 0-3.0% Cu is an element that is effective in lowering the growth and coarsening rate of the austenite phase by lowering the A1 transformation point and lowering the austenite formation temperature range. Cu is also an element that is distributed to the austenite phase. Therefore, Cu may be contained as necessary. However, if the Cu content exceeds 3.0%, the workability deteriorates and the material is prone to cracking during rolling. Therefore, the Cu content is set to 3.0% or less. The Cu content is preferably set to 2.5% or less. In order to obtain the above effect, the Cu content is preferably set to 0.3% or more.
[0040] Cr: 0~10.0% Cr is an element that is distributed to the austenite phase and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, Cr may be contained as necessary. However, if the Cr content exceeds 10.0%, an imbalance occurs between strength and ductility or strength and toughness. Therefore, the Cr content is set to 10.0% or less. The Cr content is preferably set to 8.0% or less. To obtain the above effects, the Cr content is preferably set to 0.1% or more.
[0041] Ti: 0-1.0% Ti is an element that distributes to the ferrite phase and diffuses slowly, and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, Ti may be contained as necessary. However, if the Ti content exceeds 1.0%, the steel becomes embrittled. Therefore, the Ti content is set to 1.0% or less. The Ti content is preferably set to 0.5% or less. To obtain the above effect, the Ti content is preferably set to 0.01% or more.
[0042] Nb: 0-1.0% Nb is an element that distributes to the ferrite phase and diffuses slowly, and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, Nb may be contained as necessary. However, if the Nb content exceeds 1.0%, the steel becomes embrittled. Therefore, the Nb content is set to 1.0% or less. The Nb content is preferably set to 0.5% or less. To obtain the above effects, the Nb content is preferably set to 0.01% or more.
[0043] V: 0 to 1.0% V is an element that is distributed to the ferrite phase and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, V may be contained as necessary. However, if the V content exceeds 1.0%, the steel becomes embrittled. Therefore, the V content is set to 1.0% or less. The V content is preferably set to 0.5% or less. To obtain the above effects, the V content is preferably set to 0.01% or more.
[0044] Mo: 0-2.0% Mo is an element that distributes to the ferrite phase and diffuses slowly, and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, Mo may be added as necessary. However, when the Mo content exceeds 2.0%, the effect of suppressing grain growth becomes saturated. Therefore, the Mo content is set to 2.0% or less. The Mo content is preferably set to 1.0% or less. To obtain the above effect, the Mo content is preferably set to 0.05% or more.
[0045] W: 0~1.0% W is an element that distributes to the ferrite phase and diffuses slowly, and is effective in suppressing the growth and coarsening of ultrafine austenite structures. Therefore, W may be contained as necessary. However, when the W content exceeds 1.0%, the effect of suppressing grain growth becomes saturated. Therefore, the W content is set to 1.0% or less. The W content is preferably set to 0.5% or less. To obtain the above effect, the W content is preferably set to 0.05% or more.
[0046] B: 0~0.01% B is an element that improves hardenability and is effective in obtaining a structure containing martensite. Therefore, B may be contained as necessary. However, if the B content exceeds 0.01%, toughness deteriorates. Therefore, the B content is set to 0.01% or less. The B content is preferably set to 0.005% or less. To obtain the above effects, the B content is preferably set to 0.0003% or more.
[0047] Cobalt: 0-1.0% Co is an element that is distributed to the ferrite phase and is effective in suppressing the growth and coarsening of the ultrafine austenite structure. Therefore, Co may be contained as necessary. However, when the Co content exceeds 1.0%, the effect of suppressing grain growth becomes saturated. Therefore, the Co content is set to 1.0% or less. The Co content is preferably set to 0.5% or less. To obtain the above effect, the Co content is preferably set to 0.05% or more.
[0048] Ca: 0-0.01% Magnesium: 0 to 0.01% REM: 0~0.01% Ca, Mg and REM have a pinning effect to suppress austenite grain growth and have the effect of refining austenite grains. Therefore, one or more selected from these elements may be contained as necessary. However, if the content of each of these elements exceeds 0.01%, embrittlement occurs and workability deteriorates. Therefore, the content of each element is set to 0.01% or less. In addition, when two or more elements are contained in combination, the total content may be 0.03%. In order to obtain the above effect, it is preferable to contain 0.0001% or more of one or more selected from Ca, Mg and REM.
[0049] Here, REM refers to a total of 17 elements, including Sc, Y and lanthanoids, and the content of the REM means the total content of these elements.
[0050] In the chemical composition of the steel material according to the present invention, the balance is Fe and impurities. Note that the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel material, and are permissible within a range that does not adversely affect the present invention.
[0051] Ceq: 0.10-1.00 Ceq means carbon equivalent and is defined by the following formula (i). If Ceq is less than 0.10, martensite structure cannot be obtained even if quenching is performed. On the other hand, if Ceq exceeds 1.00, not only toughness and ductility are deteriorated, but also weldability and welded part properties are deteriorated when welding is performed. Therefore, Ceq is set to 0.10 to 1.00. Ceq is preferably 0.20 or more, and more preferably 0.30 or more. Ceq=C+1 / 24Si+1 / 6Mn+1 / 40Ni+1 / 5Cr+1 / 4Mo+1 / 14V (i) In the formula, each element symbol represents the content (mass%) of each element contained in the steel, and 0 is substituted when the element is not contained.
[0052] (B) Metal structure of steel The metal structure of the steel material according to the present invention is mainly a multi-phase structure of retained austenite, martensite, tempered martensite, and bainite. Specifically, the metal structure has a total volume ratio of retained austenite, martensite, tempered martensite, and bainite of 75.0% or more. The total volume ratio of retained austenite, martensite, tempered martensite, and bainite is preferably 80.0% or more, and more preferably 85.0% or more. Structures such as ferrite and pearlite may be mixed in the steel material, but these structures are acceptable as long as their total volume ratio is 25.0% or less.
[0053] In particular, by making the matrix structure, excluding the relatively hard structures of retained austenite, martensite, and bainite, mainly of tempered martensite, it is possible to increase the yield stress (yield ratio) while ensuring ductility. Therefore, it is preferable that the volume fraction of tempered martensite is 60.0% or more.
[0054] Furthermore, when it is desired to further improve the yield ratio and elongation, the total volume fraction of the retained austenite, martensite, tempered martensite and bainite is preferably 90.0% or more, more preferably 95.0% or more. Although structures such as ferrite and pearlite may be mixed in the steel material, these structures are acceptable as long as their total volume fraction is 10.0% or less. When it is desired to further improve the yield ratio and elongation, the volume fraction of ferrite is preferably 2.5% or more. As described later, by slowing down the cooling rate, ferrite can be appropriately generated, and the yield ratio and elongation can be further improved. Moreover, the volume fraction of tempered martensite is preferably 70.0% or more.
[0055] In the following description, newly precipitated martensite may be referred to as "new martensite" to distinguish it from tempered martensite in which initial martensite has been tempered.
[0056] The volume fraction of the retained austenite in the metal structure is 5.0-15.0%, and the average crystal grain size is 2.0 μm or less. The number fraction of the retained austenite having an aspect ratio of 4.0 or more is 10-70% of the total number fraction of the retained austenite in the steel material. As described above, by including a predetermined amount of retained austenite grains with a high aspect ratio that are difficult to transform into martensite, a higher elongation improvement effect can be obtained compared to a case where the steel material is composed of only uniform grains.
[0057] Furthermore, the total volume fraction of newly formed martensite and bainite is 2.5 to 50.0%, and the average crystal grain size is 5.0 μm or less. By dispersing fine retained austenite, newly formed martensite, and bainite in a predetermined amount in the metal structure, it is possible to suppress a decrease in elongation while maintaining high strength.
[0058] The mechanical properties of steel improve with the refinement of the grain size, and the improvement is particularly remarkable when the average grain size of the newly formed martensite and bainite is 5.0 μm or less. The average grain size is preferably 3.0 μm or less. The grain size of the newly formed martensite and bainite here refers to either the prior austenite grain size or the packet grain size of the martensite and bainite, whichever can be specified.
[0059] Furthermore, when it is desired to further improve the yield ratio and elongation, the total volume fraction of newly formed martensite and bainite is preferably 2.5 to 30.0%, and the average crystal grain size is preferably 3.0 μm or less.
[0060] In the present invention, the volume fraction of each structure, the average crystal grain size, and the proportion of retained austenite grains with a high aspect ratio are measured by the following methods.
[0061] First, a sample is taken so that the cross section parallel to the rolling direction and plate thickness direction of the steel material becomes the observation surface. The observation surface is then mirror-polished and etched with a nital etching solution, after which the structure is observed using a scanning electron microscope (SEM).
[0062] At a depth position of 1 / 4 of the plate thickness of the above observation surface, an area of 300μm x 300μm is photographed at 1000x magnification. The microstructure photograph obtained is binarized to black and white and then image analyzed to identify areas judged to be newly formed martensite, bainite, or retained austenite, and the total area ratio of these is calculated using a method based on the "Microscopic Test Method for Steel-Crystal Grain Size" specified in the JIS G 0551 (2013) standard.
[0063] Next, in the same field of view (photograph), regions that are tempered martensite are identified from regions that are determined to be other than regions determined to be new martensite, bainite, or retained austenite. Ferrite, pearlite, and tempered martensite are identified based on the presence or absence of carbide precipitation. Pearlite and tempered martensite are also identified based on the shape and position of the carbides. Then, in image processing, the area ratio of the identified regions that are tempered martensite is calculated.
[0064] Next, crystal orientation is measured and analyzed using an electron backscatter diffraction (EBSD) device in the same field of view as that of the SEM observation of the same sample. The measurement is performed in an area of 30 μm x 30 μm or more, with steps of 0.05 μm or less. Then, the FCC phase is identified from the analysis results, and its area ratio is calculated based on JIS G 0551 (2013) as above, and is regarded as the area ratio of retained austenite.
[0065] The area ratio of each structure obtained by the above method is converted to a volume ratio by a line segment method based on the method described in, for example, Quantitative Microscopy, co-edited by Robert T. DeHoff and Frederik N. Rhines (1968).
[0066] The total volume fraction of the newly formed martensite and bainite is then calculated by subtracting the volume fraction of the retained austenite from the total volume fraction of the newly formed martensite, bainite and retained austenite. The total volume fraction of the newly formed martensite, bainite and retained austenite is then added to the volume fraction of the tempered martensite to calculate the total volume fraction of the retained austenite, newly formed martensite, bainite and tempered martensite.
[0067] The crystal grains identified as FCC phase are then approximated as spheroids to determine their diameter. The average grain size of the retained austenite is then calculated by averaging the diameters of all the grains in the field of view. Similarly, the crystal grains identified as FCC phase are approximated as ellipses, and the aspect ratio of each grain is determined by dividing the major axis length by the minor axis length. The proportion of the number fraction of retained austenite with an aspect ratio of 4.0 or more relative to the total number fraction of retained austenite in the steel is then determined. Note that in measuring the grain size and aspect ratio of retained austenite, grains with a circle equivalent diameter of 0.1 μm or more are targeted.
[0068] Furthermore, from the photographs taken using the above-mentioned SEM, the parts identified as retained austenite in the same field of view by EBSD measurement are removed and the image is processed to identify the structure determined to be newly formed martensite or bainite. The identified structure is then approximated as a spheroid by image analysis to determine its diameter. The average diameters of all crystal grains in the field of view are then averaged to calculate the average grain size of the newly formed martensite and bainite.
[0069] (C) Manufacturing method The steel material according to the present invention can be manufactured by subjecting a steel material having the above-mentioned chemical composition and a predetermined metal structure to a heat treatment in which the steel material is heated and then immediately cooled. Each of the conditions will be described in detail below.
[0070] <Steel material> The steel material to be used before the heat treatment has a metal structure mainly composed of martensite or tempered martensite for the following reasons.
[0071] In order to disperse many fine austenite grains during heating, it is necessary to obtain many austenite nucleation sites in advance in the metal structure. Possible nucleation sites include the grain boundaries of the initial structure and the interfaces between precipitates such as carbides and the grains of the base material. Martensite structures have substructures such as packets, blocks, and laths within prior austenite grains, and the boundaries between these structures can also become nucleation sites. Therefore, compared to ferrite / pearlite structures, martensite structures have more austenite nucleation sites, and a fine structure can be obtained during heating.
[0072] When martensite is heated, the C dissolved in the martensite precipitates as carbides before the ferrite transforms into austenite. Like austenite, carbides also precipitate preferentially at crystal interfaces within the metal structure. As mentioned above, the interfaces between the precipitated carbides and the base structure are also effective nucleation sites, so by starting with the martensite structure and heating so that austenite transformation begins after a process in which many fine carbides are formed during the heating process, more nucleation sites can be obtained.
[0073] Similarly, even when a tempered martensite structure obtained by tempering martensite is used as the starting structure, it is possible to obtain many nucleation sites.
[0074] Here, "mainly martensite or tempered martensite" means a metal structure in which the total volume fraction of martensite and tempered martensite is 95.0% or more. Although structures such as ferrite, pearlite, bainite, and retained austenite may be mixed in the steel material, these structures are allowed as long as their total volume fraction is 5.0% or less.
[0075] The method for producing the steel material is not particularly limited as long as it is possible to control the metal structure to the above structure, and any commonly used method may be used.
[0076] <Heating process> First, a steel material having the above-mentioned chemical composition and metal structure is heated to a temperature range above the Ac1 point and below (Ac1 point + 3 x Ac3 point) / 4 without recrystallization. By heating to the above temperature range, fine austenite can be generated in part of the metal structure. In addition, the remaining initial martensite is tempered to become tempered martensite.
[0077] In addition, when it is desired to further improve the yield ratio and elongation, it is preferable to first heat the steel material having the above-mentioned chemical composition and metal structure to a temperature range of Ac1 point or more and less than (Ac1 point + Ac3 point) / 2 without recrystallization. By heating to the above-mentioned temperature range, excessive recrystallization can be prevented and ferrite can be prevented from increasing excessively during cooling. By appropriately controlling the volume fraction of ferrite, the yield stress, yield ratio, and elongation can be improved. In addition, by heating to the above-mentioned temperature range, austenite can be generated more finely and the average grain size of newly formed martensite and bainite in the final structure can be reliably made fine.
[0078] There is no particular restriction on the heating rate as long as recrystallization does not occur. However, in order to reliably prevent recrystallization, the average heating rate up to the above temperature range is preferably 150°C / s or more, more preferably 500°C / s or more, and even more preferably 1000°C / s or more. There is no particular restriction on the upper limit of the average heating rate, but a practical range of 20000°C / s or less is desirable.
[0079] In the present invention, the Ac1 and Ac3 points are determined by the following method. A number of test pieces having the same chemical composition and metal structure are prepared, heated to various temperatures at a predetermined heating rate, and then cooled from the heating temperature to 70°C at an average cooling rate of 1000°C / s with a holding time of 1 s or less. Each test piece is then observed under a microscope, and the lowest heating temperature at which newly formed martensite is observed in the metal structure is defined as the Ac1 point. Furthermore, the hardness of each test piece is measured, and the heating temperature applied to the test piece at which the hardness is the maximum quenched hardness is defined as the Ac3 point. The Ac1 and Ac3 points can also be determined by measuring the thermal expansion during heating, with similar results.
[0080] <Holding process> After heating under the above conditions, cooling is started within 2 seconds. If the holding time in the above temperature range exceeds 2 seconds, austenite grows during holding, making it difficult to obtain fine newly formed martensite, bainite, and retained austenite. In addition, in the process in which austenite grows during holding, the carbon concentration in the austenite decreases as the volume fraction of austenite increases, which impairs the stability of the austenite and reduces the amount of retained austenite obtained after cooling. The above holding time is preferably 1 second or less.
[0081] <Cooling process> In the cooling process, the material is cooled to a temperature of 100°C or less so that the average cooling rate from the temperature range of the Ac1 point or more and less than (Ac1 point + 3 × Ac3 point) / 4 to 300°C is 3 to 150°C / s. If the cooling rate is less than 3°C / s, most of the austenite becomes ferrite and pearlite structure during cooling, and ultrafine martensite and bainite cannot be obtained. If the cooling rate exceeds 150°C / s, most of the austenite transforms into martensite during cooling, so that the amount of retained austenite decreases. The cooling rate may be 20°C / s or more.
[0082] On the other hand, when it is desired to further improve the yield ratio and elongation, it is preferable to cool to a temperature of 100° C. or less so that the average cooling rate from the temperature range of the Ac1 point or more and less than (Ac1 point + Ac3 point) / 2 to 300° C. is 3° C. / s or more and less than 20° C. / s. By adopting such a cooling rate, it is possible to obtain fine martensite and bainite while generating an appropriate amount of ferrite, thereby further improving the yield ratio and elongation.
[0083] By starting with martensite or tempered martensite, the structure at the start of cooling contains many linear boundaries such as packet and block boundaries. The austenite that forms at these boundaries as nucleation sites has a film-like form along the packet and block boundaries. Furthermore, the austenite that forms at the packet and block boundaries is likely to have an orientation relationship with the martensite crystals on both sides of the boundary. In this case, the interface is highly consistent, so the movement of the interface in the direction perpendicular to the interface, i.e., the growth of austenite in the width direction, is suppressed, resulting in retained austenite with a high aspect ratio.
[0084] In addition, if the starting structure is cold-rolled martensite or tempered martensite, the packet and block boundaries may be curved by cold working, and linear boundaries may decrease, making it difficult to obtain sufficient retained austenite with a high aspect ratio. Therefore, the steel material is preferably a hot-rolled steel sheet.
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0086] A 180 kg steel ingot having the chemical composition shown in Table 1 was melted in a high-frequency vacuum melting furnace and hot forged into a 30 mm thick steel slab. The resulting slab was hot rolled using a hot rolling test machine to produce a 2 mm thick hot rolled steel sheet. Various heat treatments were then performed so that the main metal structure would become the structure shown in Table 2, resulting in a steel material. A portion of the slab was further cold rolled using a cold rolling test machine to produce a 1 mm thick cold rolled steel sheet.
[0087] [Table 1]
[0088] [Table 2]
[0089] Test pieces measuring 10 mm in width, 50 mm in length, and 1 mm in thickness were cut from the obtained steel materials. Each test piece was heat treated according to the conditions shown in Table 2. Heating was performed by electrical resistance heating, and after the power supply for electrical resistance heating was cut off, the pieces were immediately cooled to room temperature by spraying cooling water. Table 2 also shows the Ac1 and Ac3 points for each material.
[0090] The metal structures of the test pieces before and after the heat treatment were measured by the following method.
[0091] First, specimens were taken from the test pieces before and after the heat treatment so that the cross sections parallel to the rolling direction and the plate thickness direction were the observation surfaces. The observation surfaces were then mirror-polished and etched with a nital etchant, after which the structure was observed using a SEM.
[0092] An image of a 300μm x 300μm area was taken at 1000x magnification at a depth of 1 / 4 of the plate thickness on the above observation surface. The microstructure image obtained was binarized to black and white and then image analyzed to identify areas judged to be newly formed martensite, bainite, or retained austenite. The total area ratio of these was calculated based on JIS G 0551 (2013) and converted to a volume ratio using the line segment method.
[0093] Next, in the same field of view (photograph), the areas that were determined to be tempered martensite were identified from the areas that were determined to be other than areas determined to be newly formed martensite, bainite, or retained austenite. Ferrite, pearlite, and tempered martensite were identified based on the presence or absence of carbide precipitation, and pearlite and tempered martensite were identified based on the shape and position of the carbides. Then, in image processing, the area ratio of the identified tempered martensite was calculated based on JIS G 0551 (2013), and converted to a volume ratio using the line segment method.
[0094] Next, the crystal orientation was measured and analyzed by EBSD in the same field of view as the SEM observation of the same sample. The measurement was performed in an area of 30 μm x 30 μm or more, with steps of 0.05 μm or less. From the analysis results, the FCC phase was identified, and its area ratio was calculated based on JIS G 0551 (2013), and converted to the volume fraction of retained austenite using the line segment method.
[0095] In addition, the crystal grains identified as FCC phase were approximated as spheroids to determine their diameters, and the average diameters of all crystal grains in the field of view were averaged to calculate the average crystal grain size of the retained austenite. Similarly, the crystal grains identified as FCC phase were approximated as ellipses, and the aspect ratio of each grain was calculated by dividing the major axis length by the minor axis length, and the proportion of the number fraction of retained austenite with an aspect ratio of 4.0 or more to the total number fraction of retained austenite in the steel was calculated. Note that in measuring the crystal grain size and aspect ratio of retained austenite, grains with a circle equivalent diameter of 0.1 μm or more were targeted.
[0096] The total volume fraction of the newly formed martensite and bainite was calculated by subtracting the volume fraction of the retained austenite from the total volume fraction of the newly formed martensite, bainite, and retained austenite. Furthermore, the total volume fraction of the retained austenite, newly formed martensite, bainite, and tempered martensite was calculated by adding the total volume fraction of the newly formed martensite, bainite, and retained austenite to the volume fraction of the tempered martensite.
[0097] Furthermore, newly formed martensite or bainite was identified by excluding the areas identified as retained austenite in the EBSD measurement in the same field of view from the photographs taken using the above-mentioned SEM and processing the images. The identified newly formed martensite or bainite was then approximated as a spheroid by image analysis to determine its diameter, and the average grain size of the newly formed martensite and bainite was calculated by averaging the diameters of all crystal grains in the field of view.
[0098] The results are shown in Table 3.
[0099] [Table 3]
[0100] Furthermore, these test pieces were subjected to a tensile test to measure the mechanical properties. The tensile test was performed using an Instron tensile tester in accordance with the provisions of the ASTM standard E8. From the above test pieces, an Instron-type tensile test piece (parallel part length: 30 mm, parallel part plate width: 6.0 mm) was taken so that the test direction was parallel to the rolling direction. In addition, since the electric heating device and cooling device used in this embodiment limited the uniform heating area obtained from a sample with a length of about 200 mm, it was decided to adopt a half-size plate-shaped test piece of the ASTM standard E8.
[0101] The results are shown in Table 4. (a) The relationship between tensile strength and yield ratio, and (b) the relationship between tensile strength and elongation are shown in Figure 1.
[0102] [Table 4]
[0103] 1(a), test numbers 6 to 10, which satisfy the requirements of the present invention, have excellent strength-ductility balance and high yield ratio. Also, test numbers 1 to 5 have almost no pearlite and ferrite of 2.5% or more, have excellent strength-ductility balance, and have better yield ratio and elongation than test numbers 6 to 10. [Industrial Applicability]
[0104] According to the present invention, it is possible to obtain a steel material having an excellent balance of strength and ductility and a high yield ratio.
Claims
1. The chemical composition, in mass%, is C: 0.03-1.00%, Si: 3.00% or less, Mn: 0.2-7.0%, P: 0.10% or less, S: 0.030% or less, Al: 3.00% or less, N: 0.010% or less, Ni: 0 to 10.0%, Cu: 0-3.0%, Cr: 0-10.0%, Ti: 0 to 1.0%, Nb: 0 to 1.0%, V: 0 to 1.0%, Mo: 0-2.0%, W: 0 to 1.0%, B: 0 to 0.01%, Co: 0-1.0%, Ca: 0-0.01%, Mg: 0 to 0.01%, REM: 0-0.01%, The balance is Fe and impurities. Ceq defined by the following formula (i) is 0.10 to 1.00, The metal structure is, in volume percent, Retained austenite: 5.0 to 15.0%; and The total volume fraction of martensite and bainite is 2.5 to 50.0%; The total volume fraction of retained austenite, martensite, tempered martensite and bainite is 75.0% or more, The average grain size of the retained austenite is 2.0 μm or less. The average grain size of martensite and bainite is 5.0 μm or less, the number fraction of retained austenite having an aspect ratio of 4.0 or more is 10 to 15% of the total number fraction of retained austenite in the steel sheet; Hot rolled steel plate. Ceq=C+1 / 24Si+1 / 6Mn+1 / 40Ni+1 / 5Cr+1 / 4Mo+1 / 14V...(i) In the formula, each element symbol represents the content (mass%) of each element contained in the steel sheet, and 0 is substituted when the element is not contained.
2. The chemical composition, in mass%, Ni: 0.1 to 10.0%, Cu: 0.3 to 3.0%, and Cr: 0.1-10.0%, Contains one or more selected from The hot rolled steel sheet according to claim 1.
3. The chemical composition, in mass%, Ti: 0.01 to 1.0%, Nb: 0.01-1.0%, V: 0.01-1.0%, Mo: 0.05-2.0%, W: 0.05-1.0%, B: 0.0003 to 0.01%, and Co: 0.05-1.0%, Contains one or more selected from The hot-rolled steel sheet according to claim 1 or 2.
4. The chemical composition, in mass%, Ca: 0.0001-0.01%, Mg: 0.0001 to 0.01%, and REM: 0.0001-0.01%, Contains one or more selected from The hot-rolled steel sheet according to any one of claims 1 to 3.
5. A method for producing a hot-rolled steel sheet according to any one of claims 1 to 4, The chemical composition according to any one of claims 1 to 4, A steel material having a metal structure in which the total volume fraction of martensite and tempered martensite is 95.0% or more, Without recrystallization, 1 point or more, and (Ac 1 Point +3×Ac 3 After heating to a temperature range of less than 100° C. / 4, cooling is started within 2 seconds, and the average cooling rate from the temperature range to 300° C. is 3 to 150° C. / s, A method for manufacturing hot-rolled steel sheets.
Citation Information
Patent Citations
High strength thin steel sheet having excellent rigidity, and its production method
JP2007092131A
High-strength cold-rolled steel sheet, and method for producing high-strength cold-rolled steel sheet
JP2008231480A
High yield ratio high strength cold rolled steel sheet and production method thereof
JP2015034326A
High strength steel sheet and method for producing the same
JP2018095896A
Steel and method for producing the same
JP2020020031A